2002
DOI: 10.1046/j.1365-2958.2002.03057.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycans mediate malaria sporozoite targeting to the liver

Abstract: Summary Malaria sporozoites are rapidly targeted to the liver where they pass through Kupffer cells and infect hepatocytes, their initial site of replication in the mammalian host. We show that sporozoites, as well as their major surface proteins, the CS protein and TRAP, recognize distinct cell type‐specific surface proteoglycans from primary Kupffer cells, hepatocytes and stellate cells, but not from sinusoidal endothelia. Recombinant Plasmodium falciparum CS protein and TRAP bind to heparan sulphate on hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
126
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(138 citation statements)
references
References 74 publications
5
126
0
3
Order By: Relevance
“…Spz may have interacted directly or indirectly with KC. According to the shift in MHC class I expression, spz affected the majority of Mac3 + KC, suggesting a rather extensive modulation, typically achievable by a soluble factor or possibly by CS protein, which binds to proteoglycans on the KC [28] and also inhibits protein synthesis [10]. Moreover, down-regulation of class I by spz in vitro appears to involve KC independent of other liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…Spz may have interacted directly or indirectly with KC. According to the shift in MHC class I expression, spz affected the majority of Mac3 + KC, suggesting a rather extensive modulation, typically achievable by a soluble factor or possibly by CS protein, which binds to proteoglycans on the KC [28] and also inhibits protein synthesis [10]. Moreover, down-regulation of class I by spz in vitro appears to involve KC independent of other liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that this arrest is mediated by the interaction between the major surface protein of sporozoites, the circumsporozoite protein (CSP) and the highly sulfated HSPGs of hepatocytes [35][36][37][38][39]. Recombinant CSP binds specifically to hepatic HSPGs and in vivo, the physiologic ligands for hepatic HSPGs, namely lactoferrin and lipoprotein remnants, delay CSP clearance from the circulation and inhibit sporozoite infection of hepatocytes [40].…”
Section: To the Livermentioning
confidence: 99%
“…The addition of sulfate moieties to HSPG GAGs is one of these modifications and as stated above, liver HSPGs are more highly sulfated compared to HSPGs from other organs [43], suggesting that the degree of GAG chain sulfation could account for the selective targeting of sporozoites to the liver. Indeed it has been found that CSP binds preferentially to cells expressing HSPGs with highly sulfated GAGs [38,39] and that sporozoite attachment to cells decreases as the degree of GAG chain sulfation decreases [38]. One confounding issue is that these highly sulfated HSPGs are found behind the endothelial cell barrier.…”
Section: To the Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Chez l'hôte vertébré, le cycle de Plasmodium passe par deux stades invasifs successifs, les stades sporozoïte et mérozoïte, qui infectent respectivement les hépatocytes et les érythrocytes ( Figure 1). Les sporozoïtes, transmis à l'hôte lors d'une piqûre par un moustique femelle du genre Anopheles, passent dans la circulation sanguine puis sont rapidement séquestrés au niveau du foie (en quelques minutes) via l'interaction de la circumsporozoite protein (CSP), protéine majeure de la surface des sporozoïtes, et de la thrombospondin-related anonymous protein (TRAP), avec les glycosaminoglycanes (GAG) proéminents dans les sinusoïdes hépatiques [1]. Les sporozoïtes traversent ensuite l'espace de Disse et pénètrent activement dans les hépatocytes, par invagination de la membrane plasmique aboutissant à la formation d'une vacuole parasitophore (Figure 2).…”
unclassified